2021
DOI: 10.1016/j.lanepe.2021.100108
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic factors and uncomplicated cystitis in women aged 15–50 years: a nationwide Swedish cohort registry study (1997–2018)

Abstract: Background Symptoms suggestive of uncomplicated cystitis constitutes one of the most common reasons to seek health care in otherwise healthy women. Previous studies regarding the relationship between sociodemographic factors and uncomplicated cystitis are limited, mainly because of the lack of nationwide population-based data from primary healthcare settings, where most uncomplicated cystitis are diagnosed. Methods A Swedish nation-wide open cohort study consisting of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 17 publications
(53 citation statements)
references
References 26 publications
2
45
2
Order By: Relevance
“…Therefore, certain groups of immigrant women might not redeem antibiotics prescribed for their infection (lack of adherence) while risking mistreating their infection with a potentially inadequate antibiotic they have at home. Moreover, we have recently observed that sociodemographic differences in uncomplicated cystitis seem to exist in largely the same population of women in Sweden [ 9 ]. However, the findings of that study [ 9 ], albeit not entirely comparable, were not consistent with the present study, and they indicate that mechanisms involved in uncertainty of diagnosis and variations in patients’ expectation could be at play.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, certain groups of immigrant women might not redeem antibiotics prescribed for their infection (lack of adherence) while risking mistreating their infection with a potentially inadequate antibiotic they have at home. Moreover, we have recently observed that sociodemographic differences in uncomplicated cystitis seem to exist in largely the same population of women in Sweden [ 9 ]. However, the findings of that study [ 9 ], albeit not entirely comparable, were not consistent with the present study, and they indicate that mechanisms involved in uncertainty of diagnosis and variations in patients’ expectation could be at play.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we have recently observed that sociodemographic differences in uncomplicated cystitis seem to exist in largely the same population of women in Sweden [ 9 ]. However, the findings of that study [ 9 ], albeit not entirely comparable, were not consistent with the present study, and they indicate that mechanisms involved in uncertainty of diagnosis and variations in patients’ expectation could be at play. For example, both women from MENA and women with higher parity had lower odds of antibiotic treatment for uncomplicated cystitis in the present study but had higher risks of uncomplicated cystitis in a recent study by our group (compared to Swedish-born women and women with no children, respectively), while the opposite was found in women from Asia (excluding the Middle East) and Oceania, who had an increased risk of uncomplicated cystitis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations